Temporal lobe parenchyma herniation: An etiological cause of headache or coexistence? (Nepal Journal of Neuroscience, 2022)
This report illustrates a patient presenting with a unilateral headache at whom brain magnetic resonance imaging showed temporal lobe parenchyma herniation. In our patient, there were no clinical or neuroimaging findings of increased intracranial pressure (ICP) that might lead to a headache. On the other hand, considering the dynamic nature of headache in our patient, we cannot exclude a mechanism of possible episodic ICP increments that might be related to encephalocele. We think that the detailed illustration of this case may present substantial perspectives for further deliberations regarding the headache pathophysiology.